2019
DOI: 10.1017/s0007485319000555
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphometric identification of pistachio psyllids with niche modeling ofAgonoscena pistaciae(Hemiptera: Aphalaridae)

Abstract: Species of Agonoscena (Hemiptera: Aphalaridae) are key pests of pistachio in all of the most important pistachio producing countries in the Old World. The efficiency and accuracy of DNA barcoding for the identification of Agonoscena species were tested using mitochondrial cytochrome c oxidase subunit 1 (mtCO1) and cytochrome b (cytb) gene sequences. Moreover, morphometric sexual dimorphism was studied. Finally, the potential geographical distribution of Agonoscena pistaciae, the most important pistachio pest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…However, the identification of P. fraxini (based on samples collected in 1902) needs to be confirmed (Burckhardt and Lauterer 1993). Also, P. machinosus has been reported from Kerman province in 2016 (Lashkari et al in press). …”
Section: Introductionmentioning
confidence: 99%
“…However, the identification of P. fraxini (based on samples collected in 1902) needs to be confirmed (Burckhardt and Lauterer 1993). Also, P. machinosus has been reported from Kerman province in 2016 (Lashkari et al in press). …”
Section: Introductionmentioning
confidence: 99%
“…Although geometric morphometrics has been used to separate species in different taxa, including Hemiptera (Shamsi Gushki et al ., 2018; Lashkari et al ., 2020), it has not been applied to Diaphorina , a psyllid genus with morphologically similar species that are notoriously difficult to identify. The forewing shape of many Diaphorina species is oblong oval, widening toward the apical quarter as in the three studied species.…”
Section: Discussionmentioning
confidence: 99%
“…In many insect groups, the COI gene serves as a good standard for barcodes (Hebert et al ., 2004a, 2004b; Hajibabaei et al ., 2006; Ashfaq et al ., 2014a, 2014b, 2015). The primers used in the current study showed their effectiveness for the studied species and were also successfully applied in other studies on Psylloidea (Percy et al ., 2016; Lashkari et al ., 2019, 2020). Although the climatic conditions vary between the collection sites, no intraspecific genetic difference was found between populations and individuals of each studied species, including all Iranian geographic populations of D. citri .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations